Proposed new interior design of Perodua 3S service centre for Medan Prisma Sdn. Bhd. Lot 10-16, 17, 18, 19, Seksyen 16, Jalan Bandar Baru Rawang, 48010 Rawang, Selangor Darul Ehsan / Muhammad Ezrin Mohd Nazan - Mohd Nazan, Muhammad Ezrin (Faculty of Architecture, Planning and Surveying, 2010)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a PROPOSED NEW INTERIOR DESIGN OF PERODUA 3S SERVICE CENTRE FOR MEDAN PRISMA SDN. BHD. LOT 10-16, 17, 18, 19, SEKSYEN 16, JALAN BANDAR BARU RAWANG, 48010 RAWANG, SELANGOR DARUL EHSAN. With the outcome of too many of local vehicles and service centre, it is hope to dedication towards social responsibility to community, the environment and development of competent workforce. The concept, style and image also applied on both interior and exterior to appeal the service centre will be able to lure more customers. There were several researches done to succeed this 3S service centre final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the PERODUA corporate image in terms of function and aesthetic value.